2013
DOI: 10.1128/jvi.02949-12
|View full text |Cite
|
Sign up to set email alerts
|

KIR2DL4Copy Number Variation Is Associated with CD4+T-Cell Depletion and Function of Cytokine-Producing NK Cell Subsets in SIV-InfectedMamu-A*01-Negative Rhesus Macaques

Abstract: Here, we demonstrate that KIR2DL4 copy number variation (CNV) is associated with CD4 + T-cell decline and functionality of cytokine-producing NK cells during primary simian immunodeficiency virus (SIV) infection in Mamu-A * 01 − Indian-origin rhesus macaques, with higher KIR2DL4 copy numbers being associated with a better preservation of CD4 + T cells and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This could be a byproduct of ambiguous mapping of short reads onto larger exon contigs. However, this observation is consistent in rhesus macaques where Hellman et al (2013) found Mamu-KIR2DL4 copy numbers varied between one and three per cell. Understanding KIR2DL4 presence/absence and copy number variation requires sequencing of more animals to identify homozygous individuals with less common KIR haplotypes.…”
Section: Discussionsupporting
confidence: 81%
“…This could be a byproduct of ambiguous mapping of short reads onto larger exon contigs. However, this observation is consistent in rhesus macaques where Hellman et al (2013) found Mamu-KIR2DL4 copy numbers varied between one and three per cell. Understanding KIR2DL4 presence/absence and copy number variation requires sequencing of more animals to identify homozygous individuals with less common KIR haplotypes.…”
Section: Discussionsupporting
confidence: 81%
“…reported an association of high copy numbers of activating KIR3DS genes with lower peak viral load in animals negative for Mamu‐A1*001 and positive for a protective TRIM5 allele. In a further study, this group demonstrated high KIR2DL4 copy numbers to be associated with a better preservation of CD4 + T cells and an increased interferon‐ γ production of stimulated CD56 − CD16 − NK cells in SIV‐infected rhesus macaques . Albrecht et al .…”
Section: The Kir and Mhc Class I Gene Families Of Macaquesmentioning
confidence: 90%
“…For example, a recent study has shown strong association of activating receptor KIR2DL4 copy number with better CD4 ? T cells recovery in SIVinfected Mamu-A*01-negative rhesus macaques [106], suggesting KIR copy number is a strong protective determinant of the disease. In the same line, a genome-wide screening of structural variants has demonstrated association of high KIR3DS1 copy number with lower viral set point in the presence of a putative ligand, while NK cells from individual with high copy number of KIR3DL1 in the presence of KIR3DS1 and ligand show efficient inhibition of HIV-1 replication [107].…”
Section: Killer Cell Immunoglobulin (Ig)-like Receptors (Kirs)mentioning
confidence: 99%